Pyroptosis, ferroptosis, and autophagy in spinal cord injury: regulatory mechanisms and therapeutic targets - Zheng, Qingcong; Wang, Du; Lin, Rongjie; Xu, Weihong (Neural regeneration research, 2025)
Regulated cell death is a form of cell death that is actively controlled by biomolecules. Several studies have shown that regulated cell death plays a key role after spinal cord injury. Pyroptosis and ferroptosis are newly discovered types of regulated cell deaths that have been shown to exacerbate inflammation and lead to cell death in damaged spinal cords. Autophagy, a complex form of cell death that is interconnected with various regulated cell death mechanisms, has garnered significant attention in the study of spinal cord injury. This injury triggers not only cell death but also cellular survival responses. Multiple signaling pathways play pivotal roles in influencing the processes of both deterioration and repair in spinal cord injury by regulating pyroptosis, ferroptosis, and autophagy. Therefore, this review aims to comprehensively examine the mechanisms underlying regulated cell deaths, the signaling pathways that modulate these mechanisms, and the potential therapeutic targets for spinal cord injury. Our analysis suggests that targeting the common regulatory signaling pathways of different regulated cell deaths could be a promising strategy to promote cell survival and enhance the repair of spinal cord injury. Moreover, a holistic approach that incorporates multiple regulated cell deaths and their regulatory pathways presents a promising multi-target therapeutic strategy for the management of spinal cord injury.